Acoustical methodology for determination of gas content in aquatic sediments, with application to Lake Kinneret, Israel, as a case study. (14th March 2017) - Katsnelson, Boris; Katsman, Regina; Lunkov, Andrey; Ostrovsky, Ilia
Abstract: The spatial distribution of gaseous methane in the top layer of the sediment of Lake Kinneret (the Sea of Galilee), Israel is quantified using a novel acoustical methodology. Measurements were carried out with low‐frequency sound pulses (200 Hz–2 kHz) for different depths of the lake along the offshore transects. The methodology is based on the correlation of gas content with sound speed and, in turn, with the reflection coefficient of sound waves from sediment. Variations in the free gas content in sediments with water depth obtained using the proposed method show a remarkable agreement with the distribution of organic matter content in and methane fluxes from sediment, both revealed by the preceding studies. This spatially variable pattern can be explained by the specific biogeochemical, hydrodynamic, and bathymetric characteristics of Lake Kinneret. The suggested method is especially suitable for characterizing gassy sediments and highlighting the location of potential methane emissions.